Craftsworkers and Canada’s First Industrial Revolution: Reassessing the Context - Kristofferson, Robert (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2005)
AbstractThis paper shows that the most remarkable aspect of the far-reaching industrial development of Hamilton, Ontario by the early 1870s was that it was achieved largely through the adaptation and expansion of pre-existing structures of production firmly rooted in the traditional crafts world. The early industrialization of Hamilton was combined and uneven, but handicraft production stood in distinction to the enlarged manufactory. “Modern Industry,” in what limited form it may have existed at all, had yet to establish itself as a typical form of industrial enterprise. All this is not surprising, since almost all those men leading the industrialization of the city were themselves former artisans and craftsworkers intimately familiar with the techniques and possibilities of craft production. This paper delineates the structures of early industrialization to suggest the pressing need for historians to reconsider the potential for continuity of craftsworker experience during early industrialization.